Factors Influencing Nurse Turnover Intentions: A Comprehensive Review of Global Evidence on Organizational, Psychosocial, and Leadership Dimensions - Melisa Anggar Fitiani; Chriswardani Suryawati; Septo Pawelas Arso (Universitas Muhammadiyah Semarang, 2025)
The stability of healthcare around the world is seriously threatened by nurse turnover intention, which is a primary predictor of actual turnover. The necessity to comprehend contributing elements is highlighted by the 47.7% new nurse turnover rate in Korea, which costs over USD 33,733 per nurse. This comprehensive review synthesizes quantitative, qualitative, and mixed-methods evidence to map factors that influence nurse turnover intention across hospital settings. Using a PRISMA-ScR approach, a literature search for